The Use of Indoglish in Faculty of Arts, Udayana University-Bali - Sedeng, I Nyoman; Indrawati, Ni Luh Ketut Mas (Journal of A Sustainable Global South; Vol 3 No 1 (2019): February 2019, 2019)
This study is aimed at 1) identifying the form of linguistic level of Indoglish commonly used in communication in Faculty of Arts, Udayana University Bali; 2) identifying the reasons of speakers when using Indoglish in the campus; and 3) analyzing the impacts of its usage on the speakers Indonesian language. As a source of data, this study uses various forms of authentic conversation that focus on the emergence of Indoglish in Faculty of Arts, Udayana University Bali, which was collected through recording and note taking techniques. In addition, the data was also gathered through filling out questionnaires by 184 respondents consisting of students, lecturers and employees in the faculty. The questionnaires focused more on questions about the respondents’ motives behind their using of Indoglish in their communication. The data was then analyzed and presented qualitatively using the theories proposed by Weinrich [1] and Holmes [2].The results of this study indicate that the form of Indoglish linguistic level used in communication between students, lecturers and staff in the Faculty of Arts of Udayana University is at 3 different levels, namely at the word level(71.96%), the level of the phrase(12.15%) and the clause / sentence level(15.89%; the dominant motives behind the use of the language are to facilitate speaking / convey intentions (34.9%) and that they do not know the correct interpretation in Indonesian (33.7%). As many as 16% of respondents stated that it is for familiarity, 10.9% to show affirmation intentions, and 1.2% used the term to express irritation; although most respondents gave a positive response to the impacts of the use of Indoglish together with their Indonesian language, it is still needed to develop a positive attitude towards the use of the correct and appropriate Indonesian in order to optimize the dynamics and poise of the language. Index Terms — linguistic level, indoglish, impact, emergence.